2005
DOI: 10.1093/ndt/gfh812
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-containing peritoneal dialysis fluids regulate leptin secretion from 3T3-L1 adipocytes

Abstract: These results suggest that the PD-induced hyperleptinaemia could, in part, be mediated by the effect of glucose-based dialysis fluids on leptin production by adipocytes via activation of the hexosamine biosynthetic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 22 publications
1
26
2
1
Order By: Relevance
“…The latter finding may be secondary to a combination of peritoneal clearance of leptin during the PD exchange test [24,57,58] and/or of circadian changes in leptinemia [59]. Intraperitoneal glucose has been demonstrated to exert a direct stimulatory effect of leptin secretion by adipocytes, but this effect may not be apparent before 24 to 48 hours after stimulation [60].…”
Section: Discussionmentioning
confidence: 99%
“…The latter finding may be secondary to a combination of peritoneal clearance of leptin during the PD exchange test [24,57,58] and/or of circadian changes in leptinemia [59]. Intraperitoneal glucose has been demonstrated to exert a direct stimulatory effect of leptin secretion by adipocytes, but this effect may not be apparent before 24 to 48 hours after stimulation [60].…”
Section: Discussionmentioning
confidence: 99%
“…Leptin activates immune system and serves as a mediator of inflammation [65]. Glucose-based PDF induces a higher leptin secretion by a murine adipocyte cell line 3T3-L1 compared to dialysate with physiological glucose concentration via the hexosamine pathway [66]. We have demonstrated that the full-length isoform of leptin receptor, Ob-Rb, is expressed in HPMC and its expression is up-regulated following exposure to glucose [67].…”
Section: Endogenous Modulatorsmentioning
confidence: 91%
“…Whether such paracrine interaction is operating between peritoneal adipocytes and MCs remains to be explored. To the best of our knowledge, there is only one previous study on the effect of PDF on adipocytes that demonstrates increased leptin synthesis in a murine adipocyte cell line (3T3-L1) by glucosecontaining PDFs [29]. It is likely that proinflammatory mediators released by MCs upon exposure to PDF could induce functional alteration of adjacent adipocytes.…”
Section: Crosstalk Between Peritoneal Cells and Adipocytesmentioning
confidence: 96%